Renal involvement and its detection in sickle cell disease children - Lakhkar, Bhavana B.; Gagneja, Karan (International Journal of Contemporary Pediatrics, 2017)
Background: Sickle cell disease is common in this part of India. Study tries to find extent of renal involvement, risk factors and screening tests in sickle cell disease. Methods: Convenient Prospective, cross sectional, observational study among known sickle cell anemia (homo and heterozygous) children and Fifty controls. Demographic and clinical findings were recorded. Renal function tests including serum sodium and potassium, eGFR were studied. Presence of microalbuminuria was checked and renal Doppler study was performed. Results: Total 110 homozygous (SS type), 55 heterozygous (AS type) and 50 normal children were recruited. Majority belonged to low socioeconomic state with male preponderance. More patients in crisis had high Urea (23%) and Creatinine (43%) than in steady state (high urea 3.38%, high creatinine 15%). In AS type children also high urea (3.6%) and creatinine (11%) was found. A subgroup in SS and AS type had lower than normal urea and creatinine. Sodium and potassium abnormality also was found in both groups. eGFR was high below 5 years and then came down. All parameters worsened with age. Renal Doppler was better indicator of renal damage than microalbuminuria. Conclusions: Renal involvement is common in sickle cell anemia. Increasing age, male sex and homozygous state were risk factors. Renal Doppler and micro-albuminuria are good screening tests. Renal Doppler was marginally superior.